THE ROLE OF FINANCIAL INCLUSION IN BRIDGING SMEs FINANCING GAP- THE VIEWPOINT OF CREDIT EMPLOYEES AT JORDANIAN ISLAMIC BANKS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to demonstrate the role of Financial Inclusion FI in bridging the financing gap in Small andmedium-sized enterprises (SMEs) from the viewpoint of credit employees at Jordanian Islamic banks. The studyused the descriptive approach in dealing with the theoretical side and the analytical method in the applied sideusing a questionnaire. The results emphasized the necessity of enhancing access to financial services as well asthe use of financial services and increasing the quality of financial services provided to SMEs to bridge thefinancing gap. The study recommended that the Central Bank of Jordan should follow up the implementation ofthe national strategy and develop legislation and regulatory systems to develop methods for obtaining financialservices for the largest number of SMEs. The study emphasized the need to facilitate legal and regulatoryprocedures to stimulate the use of modern and innovative technologies such as mobile phones and financialwallets in financial services, as well as targeting projects that are not currently serviced by the banking sector toallow access to funds at the right place and time at a reasonable cost